Az Anor-Ker Kft. logisztikai rendszere - Schäffer Barbara (2015)
The theme of this thesis is to present the functioning of logistic principles, systems and processes, which carry such a significance nowadays that these become indispensable for any company. The importance of the topic is well kown regarding to the whole industry and to operations of companies, too. In these days it would be really difficult to stay alive in any market without professional logistic solutions. During the internship a great opportunity was given to get an insight into the operations of Anor-Ker Kft. This company can be found in Szombathely, mainly dealing with trading, possessing a complex logistic activity and offering a wide range of products. This thesis will provide help in getting to know the trading activity of Anor-ker Kft. The purpose of the thesis is to introduce the logistic principles, functions and systems in practice. Aim of this study is to investigate and sum up this company functions and services. The logistics happens to be the part of every company from the beginning. The theoretical review consists of the presentation of activities regarding logistics, storage and stockpiling. After that the functions of these activities can be seen through the example of Anor-Ker Kft. At the end of the study a few suggestions are listed due to improve this company. These suggestions concern the internal information technology system, marketing advertisements, and the remodeling of the wallpaper section.